Harvard Business Review on Emerging Markets - Harvard Business School Publishing Corporation (Harvard Business Review Book, 2008)
Globalization is here to stay, and companies that avoid investing in emerging markets won't remain competitive for long. But doing business in developing regions presents unique challenges. Venture into this realm unprepared, and you may imperil your company.